Aero-Propulsive Interactions between UAV Wing and Distributed Propellers Due to Their Relative Position - Danilo Ciliberti; Pierluigi Della Vecchia; Vincenzo Orticalco; Fabrizio Nicolosi (Drones, 2023)
The purpose of this paper is the evaluation of the aero-propulsive effects on a UAV wing model with distributed propulsion. An array of three propellers is placed ahead of the leading edge of a rectangular wing with flap. The investigation was performed with high-fidelity numerical analyses to provide insights into the phenomenology and to screen the interesting positions to be validated in the wind tunnel. The propellers’ array is moved into twelve different positions, allowing longitudinal and vertical translations. The wing has an untwisted and constant section profile, with a single slot trailing-edge flap that is deflected into three positions. The flap span is entirely covered by the propellers’ blowing. Results show an increment of lift, drag, and pitching moment coefficients with distributed propellers enabled. For a given thrust level, the magnitude of such increments depends on the propellers’ positions, the flap configuration, and the angle of attack. The lift enhancement sought in distributed propulsion applications comes at the expense of a significant increase in drag and pitching moment magnitude. In some combinations, the wing’s contribution to the aircraft longitudinal stability is severely affected. Conversely, the propellers’ inflow is altered such that thrust is increased in all the investigated configurations, with a small reduction of propulsive efficiency.